Determinación de la capacidad de retención e infiltración del suelo mediante la metodología de horton para la micro cuenca del Río Pichán (Nono, Pichincha) - Tamayo Villacís, Edwin Xavier (2014)
This study determined the ability of water infiltration into the topsoil in the parish of San Miguel de Nono, specifically in the watershed of the Pichán River by Horton methodology, using as a tool the double ring infiltrate meter Muntz, where several experimental tests in each of the textures that this area of study has been performed; from soil analysis and research conducted by the Ecuadorian Space institute. For the realization of this project important factors such as temperature records and annual rainfall of 28 years, obtained from meteorological stations of the National lnstitute of Meteorology and Hydrology (INAMHI), to show that the infiltration capacity is each texture variant was analyzed to establish a strategy and land management where able to avoid or reduce water desertification caused by climate change, environmental conditions and soil salinization due to anthropogenic activities and guide the community on the generated protocol agriculture! Practices suitable. Using Geographic information Systems (SIG) mapping techniques and information gathering of the National information System, Ministry of Agriculture, Livestock, Aquaculture and Fisheries and the Ecuadorian Space lnstitute, among the most important; different types of maps indicating the general area were developed; as well as chief of the soils studied, among others, that were required for this project characteristics.